Sosialisasi dan Pendampingan Pajak Pertambahan Nilai (PPN) dan Pajak Penghasilan (PPh) Atas Transaksi Klinik Kesehatan Pada Klinik Pratama Harapan Jaya - Rolita C. Purba; Budianto Budianto; Indra Jaya; Rani Fransiska Saragih Sumbayak; Nuryustina Barasa (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
Pratama clinics, as first-level healthcare facilities, play a crucial role in providing healthcare services to the community and are also subject to tax obligations for their business activities. However, many clinics still lack a thorough understanding of Value Added Tax (VAT) and Income Tax (PPh) provisions for their transactions, particularly regarding the tax treatment of medical services, drug sales, and tax withholding and reporting obligations. This Community Service activity aims to improve Harapan Jaya Pratama Clinic's tax understanding and compliance through outreach and mentoring on VAT and PPh for clinic transactions. The implementation method includes outreach on relevant tax regulations, training in tax accounting-based transaction recording, and mentoring in identifying taxable objects, calculating, depositing, and reporting VAT and PPh in accordance with applicable regulations. The expected outcomes of this activity are increased tax literacy and awareness among clinic managers, more orderly transaction recording, and increased compliance of Harapan Jaya Pratama Clinic in fulfilling its tax obligations. This activity is expected to support better and more sustainable clinic financial governance.